Age categories differences in subjective quality of life of women with physical disabilities - Nemček Dagmar; Baňárová Patrícia Shtin; Kurková Petra (Sciendo, 2021)
The objective of the study was to analyse and compare the subjective quality of life (S-QoL) of women with physical disabilities (PDs) through satisfaction with the quality of life domains and the overall quality of life assessment.